Decrypting the Central Mystery of Quantum Mathematics:: Part 2. A Mountain of Empirical Data Supports TEW - Boyd, Jeffrey (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
The Theory of Elementary Waves (TEW) is based on three new Axioms that lead to a different understanding of quantum mathematics. There is a massive amount of research data that supports TEW. This article will take six well established experiments from mainstream scientific journals and re-interpret their axioms from a TEW point of view. Although it is usually asserted that QM explains all existing quantum experiments, that is only true if you can convince yourself that the quantum world is weird. If you adopt TEW axioms, suddenly the quantum world transforms itself into looking ordinary, like everyday Nature. If, for example, time only goes forwards, never backwards; if there is no such thing as a quantum eraser; if nothing is transmitted faster than the speed of light, then TEW axioms allow you to make sense of a quantum world which QM can only explain if you allow for weirdness throughout Nature. TEW consists of axioms that allow us to understand the quantum world in a way that makes sense from the viewpoint of our everyday experience.